2009
DOI: 10.1016/j.foodchem.2009.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein and genestein contents in tempeh and selected soy products

Abstract: a b s t r a c tThe total isoflavones in tempeh and selected local soy products was determined. Raw tempeh contained 26 ± 6 mg daidzein (Da) and 28 ± 11 mg genestein (Ge) while fried tempeh contained 35 ± 11 mg Da and 31 ± 11 mg Ge in 100 g (wet basis). Total isoflavone content in 100 g of raw tempeh, based on a dry weight, was 205 ± 56 mg and significantly reduced to 113 ± 41 mg in 100 g of fried tempeh. Tempeh in batter was deep-fried for 30 min which reduced 45% of the total isoflavone content compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 19 publications
(42 reference statements)
3
35
1
5
Order By: Relevance
“…The chemical composition of tempeh in this study was higher than that reported by Haron et al (2009), who observed, for raw tempeh, 65% average moisture, 17.5% protein, 9.2% lipid, 7.6% carbohydrate and 0.6% ash. The USDA database (United States Department of Agriculture, 2010) reports 59.6% moisture, 18.5% protein, 10.8% lipid, 9.4% carbohydrate and 1.6% ash.…”
Section: Resultscontrasting
confidence: 91%
See 3 more Smart Citations
“…The chemical composition of tempeh in this study was higher than that reported by Haron et al (2009), who observed, for raw tempeh, 65% average moisture, 17.5% protein, 9.2% lipid, 7.6% carbohydrate and 0.6% ash. The USDA database (United States Department of Agriculture, 2010) reports 59.6% moisture, 18.5% protein, 10.8% lipid, 9.4% carbohydrate and 1.6% ash.…”
Section: Resultscontrasting
confidence: 91%
“…During the first stage of fermentation (6 hours), aglycone content increased by 58% in comparison to cotyledons, and after 24-hour fermentation, both cultivars contained more aglycones in tempeh than in cotyledons. Other authors also observed that aglycone increased with fermentation time, and that after 24-hour fermentation, the amount of isoflavone aglycone doubles (Nakajima et al, 2005;Haron et al, 2009). Silva et al (2011) reported that the autoclaved whole soybean flour fermented with Aspergillus oryzae contained 36.25% of aglycones in comparison to the autoclaved whole soybean flour (6.94%), after 24 hours.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Nakashima et al (2005) also observed reduction in isoflavone content in tempeh, and Haron et al (2009) reported 43% reduction in total isoflavone in raw tempeh compared to that of fried isoflavone.…”
Section: Spectrophotometric Determination Of the Phytic Acidmentioning
confidence: 88%